Freeze-dried ammonia borane-polyethylene oxide composites: Phase behaviour and hydrogen release. (15th March 2018) - Ploszajski, A.R.; Billing, M.; Nathanson, A.S.; Vickers, M.; Bennington, S.M.
Abstract: A solid-state hydrogen storage material comprising ammonia borane (AB) and polyethylene oxide (PEO) has been produced by freeze-drying from aqueous solutions from 0% to 100% AB by mass. The phase mixing behaviour of AB and PEO has been investigated using X-ray diffraction which shows that a new 'intermediate' crystalline phase exists, different from both AB and PEO, as observed in our previous work (Nathanson et al., 2015). It is suggested that hydrogen bonding interactions between the ethereal oxygen atom (–O–) in the PEO backbone and the protic hydrogen atoms attached to the nitrogen atom (N–H) of AB molecules promote the formation of a reaction intermediate, leading to lowered hydrogen release temperatures in the composites, compared to neat AB. PEO also acts to significantly reduce the foaming of AB during hydrogen release. A temperature-composition phase diagram has been produced for the AB-PEO system to show the relationship between phase mixing and hydrogen release. Highlights: Ammonia borane and polyethylene oxide are freeze-dried to make hydrogen storage composites with high hydrogen content. Mixing ammonia borane and polyethylene oxide produces a new crystalline phase. It dehydrogenates with a different reaction pathway to pure ammonia borane. Hydrogen bonding between the species promotes this hydrogen release reaction. Polyethylene oxide reduces foaming of ammonia borane during hydrogen release.